Challenges for the new century : international insertion and regional integration in a globalization scenario - Vacchino, Juan Mario (2000)
Examines both the characteristics of the globalization process and its impact on the countries of Latin America and the Caribbean and the measures and policies these have adopted to insert themselves into the international community.